PENINGKATAN KEMAMPUAN MENCERITAKAN KEMBALI CERITA PENDEK MATA PELAJARAN BAHASA INDONESIA DENGAN METODE DISKUSI PADA SISWA KELAS IX.A SMPN 11 MUARO JAMBI - Salipah Saiyah (Indonesian Journal of Teacher Education, 2020)
This research was motivated by the low ability to retell short stories (short stories) in Indonesian language lessons for class IX.A students of SMPN 11 Muaro Jambi. This study aims to improve the ability to retell short stories in Indonesian language lessons with the discussion method for class IX.A students of SMPN 11 Muaro Jambi. The subjects of this study were all students of class IX.A SMPN 11 Muaro Jambi, totaling 30 people, for the 2018/2019 academic year. The form of research is Classroom Action Research. The research instrument consisted of performance instruments and data collection instruments in the form of teacher activity observation sheets and student activities. Based on the results of the study, the conclusion of this study is to improve the ability to retell short stories (short stories) with the discussion method for students IX.A SMPN 11 Muaro Jambi. The average student on the initial test was categorized as moderate with an average value of 71.00, with a percentage value of 30% completeness or there were 9 students who were declared complete and the remaining 21 students were declared incomplete with a percentage of 70%, In cycle I, the average ability value -The mean of students rose to 78.6 in the medium category, with a percentage value of 53.3% or a total of 16 students, in cycle II the average ability of students was categorized as high with an average score of 82.16 with completeness of 90% , where students' completeness scores have been achieved. The above statement shows that the ability to retell short stories (short stories) with the discussion method of students IX.A SMPN 11 Muaro Jambi can be improved through the discussion method, thus the research hypothesis which reads: "Improved ability to retell short stories (short stories) with discussion method. Students IX.A SMPN 11 Muaro Jambi can be "accepted".